The theoretical aspects of modeling the management of educational resources of higher education in Ukraine - Фадєєв, Владислав Іванович (Pedagogy of Higher and Secondary Education, 2013)
Fadeev V. I. The theoretical aspects of modeling the management of educational resources of higher education in Ukraine This article analyzes the characteristics of theoretical modeling of management of educational resources of higher education. The features of a systems approach to modeling the management of educational resources of higher education in Ukraine are researched.